The effects of whole-body alternating current magnetic treatment on blood lactate concentration after high intensity intermittent exercise - Nakamura, D.; Suzuki, S.; Wakamura, T. (International Journal of Sport & Health Science, 2004)
The aims of this study was to examine the effects of whole-body alternating current magnetic treatment on the removal of blood lactate concentration and subsequent performance after high intensity intermittent exercise. Seven male collegiate soccer players were participated in this study. High intensity intermittent exercise was consisted of 5-s maximal effort cycle ergometer exercise bout repeated 8 times with 20-s rest (Exercise 1). After 30 minutes rest, the subjects performed same exercise (Exercise 2). The subjects were randomly assigned to whole-body alternating current magnetic treatment (Ex.) or not whole-body alternating current magnetic treatment (Con.) for 30 min during the rest period and vice versa. Blood samples were taken from a fingertip to determine blood lactate oncentration at immediately, 5, 10, 15, 20, 25, and 30 minutes after exercise 1. There was signifi cant difference of removal rate of blood lactate concentration between both groups at early stage (within 10 minutes) during rest period after Exercise 1. However, there were no significant changes in total power output of cycle ergometer at 2nd set between both groups. In conclusion, whole-body alternating current magnetic treatment after high intensity intermittent exercise had supposed to effect on the removal rate of blood lactate concentration at early stage and no effect on subsequent performance.